2013
DOI: 10.1118/1.4816658
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optimization of dose distributions and fractionation schemes in particle radiotherapy

Abstract: The paper provides conceptual insight into the interdependence of optimal fractionation schemes and the spatial optimization of dose distributions. It demonstrates the emergence of nonuniform fractionation schemes that arise from the standard BED model when IMPT fields and fractionation scheme are optimized simultaneously. Although the projected benefits are likely to be small, the approach may give rise to an improved therapeutic ratio for tumors treated with stereotactic techniques to high doses per fraction. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Thereby, high single fraction doses are delivered to parts of the target volume while simultaneously achieving fractionation in surrounding normal tissues, providing a net improvement of the therapeutic ratio. The use of such nonuniform spatiotemporal fractionation schemes has previously been demonstrated for proton therapy [11,12]. For proton beams, the entrance dose is mostly independent of the proton range, which provides the opportunity to move dose from proximal to distal parts of the target volume without changing the dose in the entrance region.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, high single fraction doses are delivered to parts of the target volume while simultaneously achieving fractionation in surrounding normal tissues, providing a net improvement of the therapeutic ratio. The use of such nonuniform spatiotemporal fractionation schemes has previously been demonstrated for proton therapy [11,12]. For proton beams, the entrance dose is mostly independent of the proton range, which provides the opportunity to move dose from proximal to distal parts of the target volume without changing the dose in the entrance region.…”
Section: Introductionmentioning
confidence: 99%
“…This is in particular the case for liver toxicity endpoints because both fractionation effects and dose-volume effects need to be accounted for in outcome modeling. Generally, it is expected that the benefit of spatiotemporal fractionation over uniform fractionation decreases with lower α / β -ratio for the liver whereas a higher liver α / β -ratio is in favor of spatiotemporal fractionation [14]. However, the dependence of mean liver BED reductions on the α / β -ratio is weak within the range of typically assumed values, which was confirmed by treatment planning experiments.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, it has been shown that this goal can be achieved to some degree by delivering distinct dose distributions in different fractions. The concept has been named spatiotemporal fractionation [1114]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mizuta et al have proposed a mathematical method to select a fractionation regimen based on physical dose distribution, 18 and relevant investigations into this have been reported subsequently. [19][20][21][22] Following the paper, 18 the authors also presented a graphical method using a "TO plot" to determine the appropriate fractionation regimen based on the relation between radiation effects on the tumor and an organ at risk (OAR). 23 These studies have shown explicit criteria for selecting better fractionation methods, which are determined by the physical dose distribution and the α/ β value in the linear-quadratic (LQ) model.…”
Section: Introductionmentioning
confidence: 99%